2020
DOI: 10.1523/eneuro.0234-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-DOPA on Gene Expression in the Frontal Cortex of Rats with Unilateral Lesions of Midbrain Dopaminergic Neurons

Abstract: The development of Parkinson's disease (PD) causes dysfunction of the frontal cortex, which contributes to the hallmark motor symptoms and is regarded as one of the primary causes of the affective and cognitive impairments observed in PD. Treatment with L-DOPA alleviates motor symptoms but has mixed efficacy in restoring normal cognitive functions, which is further complicated by the psychoactive effects of the drug. We investigated how L-DOPA affects gene expression in the frontal cortex in an animal model of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Indeed, the TRAP-RNAseq model has led to the discovery of previously unknown distinct MSN subpopulations involved in locomotor control (Fieblinger, 2021). Third, while our study focused on changes in gene expression in the striatum, other studies have demonstrated that chronic LDOPA can induce changes in gene expression in other areas of the brain such as the frontal cortex, as well as in cell types other than MSNs, including immune and endothelial cells (Radlicka et al, 2021). Lastly, our study did not consider changes in DNA methylation which have been implicated in the development and maintenance of LID (Figge et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the TRAP-RNAseq model has led to the discovery of previously unknown distinct MSN subpopulations involved in locomotor control (Fieblinger, 2021). Third, while our study focused on changes in gene expression in the striatum, other studies have demonstrated that chronic LDOPA can induce changes in gene expression in other areas of the brain such as the frontal cortex, as well as in cell types other than MSNs, including immune and endothelial cells (Radlicka et al, 2021). Lastly, our study did not consider changes in DNA methylation which have been implicated in the development and maintenance of LID (Figge et al, 2016).…”
Section: Discussionmentioning
confidence: 98%